Shelf-Life Estimation of Black, Red and Yellow Honey Coffee Using Critical Moisture Content Approach - Dyah Ayu Savitri; Setiyono; Ayu Puspita Arum; Susan Barbara Patricia Sembiring Meliala; Fauziatun Nisak; Sean Zheva Danuartha (Journal of Applied Agricultural Science and Technology, 2026)
Honey process is a newly developed coffee processing technique. Based on the washing intensity, honey coffee categorized into black, red, and yellow honey coffee. Once the green bean coffee obtained, they are roasted then ground. However, the shelfs-life of Arabica honey-processed ground coffee has not yet been estimated. Therefore, this study aimed to predict the shelf life of Arabica honey-processed ground coffee (black, red, and yellow honey) using the critical moisture content approach. The analysis in this study was conducted descriptively so that it can explain the predicted shelf life of honey ground coffee stored in metallized plastic packaging. The results indicated that the critical moisture content for yellow, red, and black honey ground coffee products was 5.55% (db), 7.44% (db), and 8.51% (db), respectively. The moisture sorption isotherm (MSI) curves were described by the linear equations y = 1.0672x - 0.741 for yellow honey, y = 2.3315x - 1.6017 for red honey, and y = 0.55x - 0.308 for black honey. Using the Labuza equation at 80% relative humidity (RH) and 30°C, the estimated shelf life of Arabica ground honey coffee in metallized plastic packaging ranges from 2.51 to 2.67 years.